Alcohol-related sexual violence perpetration toward sexual and gender minority populations: a critical review and call to action - Parrott, Dominic J. (Alcohol and sexual violence, 2023)
Sexual violence perpetrated toward sexual and gender minority (SGM) individuals is a significant public health problem. Although proximal alcohol use is one of the most well-established contributors to sexual violence perpetration toward heterosexual, cisgender women, its effects on the perpetration of sexual violence toward SGM individuals are rarely studied and, as a result, poorly understood. In this chapter, we aim to catalyze work in this area by advancing an integrative theoretical model of alcohol-facilitated sexual violence perpetration toward SGM individuals. Situated in a heuristic stigma-based framework, the proposed integrative model (1) organizes risk and resilience factors across the social ecology, and (2) explains the proximal mechanisms by which alcohol use facilitates sexual violence perpetration toward SGM individuals. This integrated model is used to inform our “call to action” that includes recommendations to strengthen the rigor of future research, with a particular focus on assessment of the proximal and temporal effects of alcohol on sexual violence perpetration. Additionally, we identify theoretical-based targets for prevention at multiple levels of the social ecology.